Antigen Discovery in Circulating Extracellular Vesicles From Plasmodium vivax Patients - Aparici-Herraiz, Iris; Gualdrón-López, Melisa; Castro-Cavadía, Carlos J.; Carmona-Fonseca, Jaime; Yasnot, María Fernanda; Fernandez-Becerra, Carmen; del Portillo, Hernando A. (Frontiers in Cellular and Infection Microbiology, 2022)
Plasmodium vivax is the most widely distributed human malaria parasite with 7 million annual clinical cases and 2.5 billion people living under risk of infection. There is an urgent need to discover new antigens for vaccination as only two vaccine candidates are currently in clinical trials. Extracellular vesicles (EVs) are small membrane-bound vesicles involved in intercellular communication and initially described in reticulocytes, the host cell of P. vivax, as a selective disposal mechanism of the transferrin receptor (CD71) in the maturation of reticulocytes to erythrocytes. We have recently reported the proteomics identification of P. vivax proteins associated to circulating EVs in P. vivax patients using size exclusion chromatography followed by mass spectrometry (MS). Parasite proteins were detected in only two out of ten patients. To increase the MS signal, we have implemented the direct immuno-affinity capture (DIC) technique to enrich in EVs derived from CD71-expressing cells. Remarkably, we identified parasite proteins in all patients totaling 48 proteins and including several previously identified P. vivax vaccine candidate antigens (MSP1, MSP3, MSP7, MSP9, Serine-repeat antigen 1, and HSP70) as well as membrane, cytosolic and exported proteins. Notably, a member of the Plasmodium helical interspersed sub-telomeric (PHIST-c) family and a member of the Plasmodium exported proteins, were detected in five out of six analyzed patients. Humoral immune response analysis using sera from vivax patients confirmed the antigenicity of the PHIST-c protein. Collectively, we showed that enrichment of EVs by CD71-DIC from plasma of patients, allows a robust identification of P. vivax immunogenic proteins. This study represents a significant advance in identifying new antigens for vaccination against this human malaria parasite.